High prevalence of clonal hematopoiesis‐type genomic abnormalities in cell‐free DNA in invasive gliomas after treatment. Issue 11 (5th February 2021) - Okamura, Ryosuke; Piccioni, David E.; Boichard, Amélie; Lee, Suzanna; Jimenez, Rebecca E.; Sicklick, Jason K.; Kato, Shumei; Kurzrock, Razelle
Abstract: Plasma cell‐free DNA (cfDNA) is emerging as an important diagnostic tool in cancer. However, cfDNA alterations may differ from those in tissue and sometimes may reflect processes unrelated to the cancer, including clonal hematopoiesis (CH). We examined plasma cfDNA, tested by next‐generation sequencing (NGS), for characterized alterations (excluding variants of unknown significance) in 135 patients with invasive glioma. Overall, 21% (28/135) had ≥1 alteration; 17% (23/135) had CH‐type cfDNA mutations. Temozolomide (a mutagenic alkylating agent) with concurrent radiation therapy prior to blood draw was significantly associated with an increase in CH‐type mutations, even after age, race/ethnicity, and WHO‐grade were considered as confounders (odds ratio [95% confidence interval, CI] 8.98 [1.13‐71.46]; P = .04; multivariable analysis). Further, of 18 patients with invasive glioma who had both cfDNA and tissue DNA NGS and had ≥1 cfDNA alteration, 16 (89%) had ≥1 cfDNA alteration not found in their tissue DNA, including CH‐type alterations in genes such as TP53 (most common), ATM, GNAS, and JAK2 . Altogether, 87% of cfDNA alterations (20/23) observed in the 18 patients were implicated in CH. Finally, examining all 135 patients, CH‐type cfDNA mutations were an independent prognostic factor for shorter survival (hazard ratio [95% CI] 3.28 [1.28‐8.40]; P = .01). These findings emphasize that not all characterized cfDNA alterations detected in patients with solid tumors are cancer‐related. Importantly, in patients with invasive gliomas who have had prior temozolomide and radiation, CH‐related alterations in cfDNA are frequent and correlate with poor outcomes. Abstract : What's new? Tissue biopsy for brain tumors presents significant challenges, making less‐invasive molecular profiling with plasma cell‐free DNA (cfDNA) an appealing alternative. However, whether alterations detected in cfDNA, including clonal hematopoiesis (CH), reflect processes in brain tumor tissue remains uncertain. In this investigation of CH‐associated mutations in plasma‐derived cfDNA from patients with invasive gliomas, 87 percent of characterized cfDNA alterations were implicated in CH, indicating that not all cfDNA alterations are cancer‐related. In addition, temozolomide/radiation therapy prior to blood draw for cfDNA was associated with potential CH‐type cfDNA mutation detection. Potential CH‐type cfDNA alterations were an independent predictor of shorter overall survival.